Violation of the principle of progressivity and non-regressivity with the issuance of legislative act 01 of 2005 against the general pension system in Colombia - Gerson Yahir Vergel Ramirez; Jarvi Amaya Amaya; Leonardo Fabio Quintero Torres (Postulados: Revista Sociojurídica)
Through this article it is intended to apply analytical methods purely to legal issues, that is, to divide them into as many parts as possible. This means that, unless other fines are pursued, the object must be clearly defined (ANALYSIS OF INEQUALITY OF LEGISLATIVE ACT 01 OF 2005 WHERE TABLE 14 OF NEW PENSIONERS IN COLOMBIA IS ELIMINATED). The promulgation of legislative act No. 01 of 2005, led to situations not conducive to the labor law, such as the abolition of allowance 14 for new pensioners in Colombia. Suppressing the rights that workers who believe they have reasonable expectations of a pension have won, and it also violates the principle of equality established in article 13 of the Fundamental Charter, since currently some pensioners do have allowance 14 and others do not. In this sense, this document aims to analyze the constitutionality of legislative act No. 01 of 2005 and compare it with reasonable expectations of pensions in the medium premium system; to achieve the proposed goal. In addition, the principle of financial sustainability has not had immediate effects, since since the enactment of the legislative act the imbalance of the Average Premium Regime persists